A New Concept of Teaching Vocabulary in EFL Classroom by Utilizing Language Reactor Toolbox On Chrome Extension - Fakhrurriana, Ria; Nasrullah , Naufal Siddiqi (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
In the field of ELT, the issue in lack of vocabulary has emerged as a major obstacle. Thus, the purpose of this article was to discuss Language Reactor Toolbox (LRT) as a new concept for vocabulary teaching in EFL classrooms and how LRT can be utilized to address the problem in vocabulary teaching. The conceptual research design employed in this work was focused on conceptual models and specifically utilized conceptual description. This article signified for academics to support the literature review as references for their empirical researches. The findings showed that LRT became a new concept of vocabulary teaching to increase students' interest in vocabulary learning. Moreover, the present article provided a gateway to the empirical study of LRT on chrome extension for vocabulary teaching. Future research could examine on the impact LRT in vocabulary teaching of EFL classroom.